What is Reflection-In-Action? A Phenomenological Account - Yanow, Dvora; Tsoukas, Haridimos (Journal of management studies, 2009)
Building on the work of Donald Schön and phenomenological treatments of practice, we propose a phenomenological theory of reflection‐in‐action that develops this concept further, thereby transcending a number of limitations we find in his theorizing. Our theory includes: an appreciation for the evaluative dimensions built into competent practice that encourage, if not require, reflecting; a further theorizing of the character of surprise; and a fuller delineation of the character of improvisation in relation to practice and its surprises. We begin with a phenomenological account of cognition in relation to work, especially in its form of professional practice. We reframe Schön's arguments in phenomenological, especially Heideggerian, terms and take account of relatively recent theorizing about knowledge‐based work, illustrating these discussions with a vignette drawn from field research in the world of practice. We conclude with a discussion of the implications of these arguments for practitioners as well as for further theorizing.